Analytical Method Development and Validation for the Estimation of Related Substances in Oxybutynin HCl Prolonged Release Tablets by Reverse-Phase High- Performance Liquid Chromatographic: Analytical Method Development and Validation for the Estimation of Related Substances in Oxybutynin HCl Prolonged Release Tablets by Reverse-Phase High- Performance Liquid Chromatographic - Natraj, K. S. (International Journal of Pharmaceutical & Biological Archive, 2018)
Reverse-phase high-performance liquid chromatographic method has been developed for the determination of related compound of oxybutynin hydrochloride in pure form and pharmaceutical dosage forms. Isocratic elution at a flow rate of 1.0 ml/min was employed on a primesil-C18 column (150 Ã— 4.6 mm, 3.5 Î¼m SS) at 45Â°C. The mobile phase consisted of mixture of water:acetonitrile:triethylamine in the ratio of 690:310:2 (%V/V), respectively, and the ultraviolet detection wavelength was 210 nm. The RT value of oxybutynin hydrochloride, impurity-D, and impurity-A was found to be 13.75 min, 19.80 min, and 24.89 min, respectively, with a run time of 60 min. The developed method was validated for linearity, accuracy, precision, detection limit, quantification limit, robustness, specificity, and system suitability. Results of all validation parameters were within the limits as per ICH guidelines.